Cash Waqf Linked Sukuk (CWLS) Model: For Indonesia Sustainable Food Security - Patria Yunita (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2020)
This study aims to build an integrated model between Islamic social finance, government sukuk financing and Indonesian food security. This study proposes an integrated model between Islamic social finance and government sukuk to build community food security through the cash waqf linked sukuk model. This model based on a modification of Sukuk issued by The Central Bank of Bahrain to provide a commodity in the future. The model proposed in this study is an innovative productive waqf model. The management involves both government and private companies. Sukuk are issued by the government through the ministry of finance or Bank Indonesia. Sukuk issued in social purposes with the underlying transaction is an innovative productive waqf. After the sukuk is issued, the funds are collected by means of a waqf contract, through cash waqf and assets. The funds or assets collected are submitted to the operational manager. The operational manager provides sukuk funds to farmers as capital for carrying out agricultural, plantation and livestock activities. Products that are prioritized are the primary needs of the community, including agricultural products of superior quality from biotechnology research, superior quality vegetables from biotechnology research in the field of plantations, livestock products from research field. The harvest is sold through the ministry of agriculture or through the traditional market to support the availability of food in sufficient quantities in a minimum price. The preferred products are the products of the primary needs of the community.